White sage, bears, and territory contemporary indigenous religion among the Chumash - Paldam, Ella (Journal of contemporary religion, 2018)
Since the 1960s, indigenous revitalization has been widespread in Native North America. However, few systematic studies of contemporary indigenous religion exist. This article provides an in-depth analysis of revitalized beliefs and practices as they are lived among the Chumash of Southern California. Shaped by a colonial history that almost eradicated indigenous culture, Chumash tradition is reinterpreted through religious practices that ground it in local territory and anchor it in pre-Catholic traditions. Although postcolonial agendas are significant in indigenous Chumash religion has existential significance beyond ethnicity politics. Contemporary Paganism is employed as a comparative perspective to discuss how religion provides a way for individuals to define and explore their cultural specificities when they relate to and participate in globalized society. The practices of healing, cleansing, and divination as well as beliefs in the unity with animals, spirits, and ancestors form a framework not only for individuals' search for meaning, but also for reestablishing community.